2020
DOI: 10.1038/s41598-020-58199-w
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-free and synergistic interaction of ultrasound combined with plasma-activated water (PAW) to enhance microbial inactivation in chicken meat and skin

Abstract: In general, the poultry industry uses 0.5-1 ppm chlorine solution in the meat sanitization process. However, chlorine can react with organic material and produce halogenated organic compounds, notably chloroform, which causes bladder and rectal cancer in humans. For this reason, many industries try to avoid chlorine. This study investigated the efficacy of ultrasound and plasma-activated water (pAW) on the inactivation of Escherichia coli and Staphylococcus aureus in chicken muscle, rough skin, and smooth skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 37 publications
8
60
0
Order By: Relevance
“…The study showed that PAW ice efficiently inhibited the growth of microorganisms and slowed down the quality deterioration of shrimps, indicating a promising method to extend the shelf‐life of shrimps and other seafood products. Royintarat, Choi, Boonyawan, Seesuriyachan, and Wattanutchariya (2020) investigated the efficacy of US‐assisted PAW on the inactivation of E. coli and S. aureus on chicken muscle, rough skin, and smooth skin. Up to 1.33 and 0.83 log reduction for E. coli and S. aureus was achieved after the combined treatment, and the porous structure on chicken muscle facilitated the penetration of PAW.…”
Section: Potential Applications Of Paw In the Food Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…The study showed that PAW ice efficiently inhibited the growth of microorganisms and slowed down the quality deterioration of shrimps, indicating a promising method to extend the shelf‐life of shrimps and other seafood products. Royintarat, Choi, Boonyawan, Seesuriyachan, and Wattanutchariya (2020) investigated the efficacy of US‐assisted PAW on the inactivation of E. coli and S. aureus on chicken muscle, rough skin, and smooth skin. Up to 1.33 and 0.83 log reduction for E. coli and S. aureus was achieved after the combined treatment, and the porous structure on chicken muscle facilitated the penetration of PAW.…”
Section: Potential Applications Of Paw In the Food Industrymentioning
confidence: 99%
“…Moreover, an increased lipid oxidation was reported for shrimps after PAW ice treatment (Liao et al., 2018), frozen beef after thawing by PAW (Liao et al., 2020), and fresh beef after PAW treatment (Zhao et al., 2018) due to the oxidative stress in PAW. Regarding physical parameters change after PAW treatment, less areas of blackspot in shrimps, a decreased a: value (redness) for fresh beef (Zhao et al., 2018), and distinct changes of color for chicken meat were reported (Royintarat et al., 2020). However, not all the PAW treatments resulted in remarkable quality changes.…”
Section: Potential Applications Of Paw In the Food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Types of working gases could influence the concentration of the reactive species produced in PAW (Lukes, Dolezalova, Sisrova, & Clupek, 2014). Several working gases, such as air, Ar, He, and Ar/O 2 , have been successfully reported to generate PAW (Lin et al., 2019; Royintarat, Choi, Boonyawan, Seesuriyachan, & Wattanutchariya, 2020; Royintarat et al., 2019; Vlad et al., 2019). Vlad et al.…”
Section: Generation Of Pawmentioning
confidence: 99%
“…Microbial parameters include the type and state of the micro-organism, for example, vegetative bacteria or spores, planktonic or detached state (Kamgang-Youbi et al 2008;Smet et al 2019), and the microbial community on food products may also affect the inactivation efficacy. Regarding abiotic parameters, storage temperature for PAW (Shen et al 2016;Han et al 2016b), the presence of organic materials in water (Ryu et al 2013;Xiang et al 2019;Zhao et al 2020), and the surface morphology of food products (Royintarat et al 2020) should be considered.…”
Section: Introductionmentioning
confidence: 99%